A supervulnerabilidade da mulher migrante e trabalhadora no Brasil - Martins, Lilia (2024)
This research focuses on the supervulnerability1 of migrant and working women in Brazil, addressing the complex reality of these migrant women, with a focus on their insertion and recognition in the formal labor market. The proposed problem is: What are the consistent implications of social inequalities for migrant women when entering the formal labor market? The hypotheses point to the challenges faced by these women, largely due to the absence of adequate public policies and/or insufficient attention to their specific needs. The objective is to investigate the implications for the insertion of these women in the labor market, analyze the aspects of migration in Brazil, understand the history of migration, the feminization of this process, and highlight their struggle for recognition. Using a documentary approach and an interdisciplinary literary narrative, using the deductive method, it was possible to confirm the hypotheses raised and conclude that, even with the advances provided by globalization, many migrant women continue to be directed to precarious and undervalued work positions, mainly in the informal sector and in occupations traditionally associated with the female role. Domestic and unpaid work, as well as occupations of less complexity, remain the predominant options for these women, which perpetuates a cycle of exploitation and devaluation.